Characterization of glycosylation regulator-mediated glycosylation modification patterns and tumor microenvironment infiltration in hepatocellular carcinoma - Zhao, Linlin; Guo, Yang; Liu, Zhanfeng; Ma, Jing; Peng, Yanfeng; Zhang, Dejun (Frontiers in Genetics, 2022)
Background: Previous studies have shown that glycosylation of proteins ofen plays an important role in HCC. However, the potential mechanism of glycosylation in HCC has not been described systematically. Methods: We comprehensively evaluated the glycosylation patterns in HCC samples based on 43 glycosylation regulators, and annotated the different modification patterns with the enrichment of immune cells and stromal cells. Considering the heterogeneity of HCC patients, the glycosylation score was constructed by ssGSEA. More importantly, we explored the sensitive drugs of different HCC patients based on the glycosylation mode and glycosylation score. Results: This study identified a glycosylation regulated gene subtypes with three subtypes. By annotating the subtypes, it was found that the glycosylation regulated gene subtypes was highly matched with the three immunophenotypes of HCC (immune-inflamed, immune-excluded and immune-desert) regardless of the characteristics of immune cell infiltration or prognosis. Based on the characteristic genes of the glycosylation regulated gene subtypes, we constructed a glycosylation related model, and found that the glycosylation related model was highly consistent with the glycosylation regulated gene subtypes. The glycosylation score that evaluates the glycosylation characteristics of a single HCC sample has high prognostic value, and the prognosis of patients with high glycosylation score is significantly worse. Interestingly, we found that glycosylation score was closely related to TNM staging. Applying glycosylation regulated gene subtypes and glycosylation score to explore the sensitivity of different patients to anticancer drugs, it was found that the sensitivity of Thapsigargin，Shikonin, Embelin and Epothilone.B was closely related to the glycosylation mode. Conclusion: This study reveals that the diversity of glycosylation patterns plays an important role in HCC. Evaluating the glycosylation patterns of of HCC patients is helpful to identify the characteristics of immune cell infiltration and select accurate treatment methods.